Three-dimensional high aspect ratio interface elements for simulating 3D hydraulic fracturing in deformable porous media - Cleto, Pedro R. [UNESP]; Camargo, Murilo [UNESP]; Maedo, Michael A.; Rodrigues, Eduardo A. [UNESP]; Manzoli, Osvaldo L. [UNESP] (Elsevier, 2023)
Hydraulic fracturing (HF) is a technique widely used in the oil industry to stimulate low permeability reservoirs and enable their production. However, to model the HF is necessary to consider at least three main coupling process: (i) the fluid pressure deforming the fracture walls, (ii) the fluid flow inside the fracture, and (iii) the fracture propagation through the porous medium. In this context, this work aims to expand the applicability of the high aspect ratio interface elements (HAR-IE) to simulate the formation and propagation of induced hydraulic fracture in three-dimensional scenarios. The proposed methodology considers a deformable porous media in which the fluid flow is governed via Darcy's law. A proper tension continuum damage model is employed to deal with the fracture formation process and the classical cubic law defines the fluid flow in the fracture. A fully-coupled method solves the system of equations and the numerical results focus on the validation of the method via comparisons against analytical solutions. All the results showed that 3D HAR-IEs satisfactorily reproduce the main characteristics associated with HF, as fracture aperture, length and injection pressure.
Keywords: 3D hydraulic fracturing; Deformable porous media; Fracture propagation; High aspect ratio interface element; Hydro-mechanical coupling